H0LiCOW VIII. A weak-lensing measurement of the external convergence in the field of the lensed quasar HE 0435−1223. Issue 4 (26th April 2018) - Tihhonova, O; Courbin, F; Harvey, D; Hilbert, S; Rusu, C E; Fassnacht, C D; Bonvin, V; Marshall, P J; Meylan, G; Sluse, D; Suyu, S H; Treu, T; et al.
Abstract: We present a weak gravitational lensing measurement of the external convergence along the line of sight to the quadruply lensed quasar HE 0435−1223. Using deep r -band images from Subaru Suprime Cam, we observe galaxies down to a 3σ limiting magnitude of ∼26 mag resulting in a source galaxy density of 14 galaxies per square arcminute after redshift-based cuts. Using an inpainting technique and multiscale entropy filtering algorithm, we find that the region in close proximity to the lens has an estimated external convergence of κ =-0.012^+0.020_-0.013 and is hence marginally underdense. We also rule out the presence of any halo with a mass greater than M vir = 1.6 × 10 14 h −1 M ⊙ (68 per cent confidence limit). Our results, consistent with previous studies of this lens, confirm that the intervening mass along the line of sight to HE 0435−1223 does not affect significantly the cosmological results inferred from the time-delay measurements of that specific object.